Exploration on the Reform Path of Innovation and Entrepreneurship Practice Education for Engineering Students in Local Universities - Wang, Peng; Qu, Xiaoya; Li, Na; Sun, Jinfeng (Transactions on Social Science, Education and Humanities Research, 2024)
In view of the serious shortage of practical education compared with theoretical education in the current innovation and entrepreneurship education in local colleges and universities in China, this paper explores and practices how to carry out the practical education of mass innovation and innovation for engineering students in local colleges and universities. This paper analyzes the talent training objectives, the characteristics of students and the practice of entrepreneurship and innovation education in local colleges and universities, summarizes the common problems existing in the education of engineering students in local colleges and universities, puts forward reform measures and solutions, and carries out practice.